PENENTUAN KINETIKA ENZIM POLIGALAKTURONASE (PG) ENDOGENOUS DARI PULP BIJI KAKAO - GANDA PUTRA, G.P. (Jurnal Biologi Udayana, 2009)
This research was conducted to determine the enzyme kinetics (Km and Vmax) of endogenous polygalacturonase (PGs) isolated from cocoa pulp. This research was carried out by assaying PGs activities in various concentration of citrus pectin subtrates which were between 0,1 – 1,0% with 0,1% interval. The result showed that the enzyme kinetics of endogenous PGs from cocoa pulp (Km) was 0,37% and Vmax was 6,69 µmol of galacturonic acid/minute/ml.
Keywords: enzymatic kinetics (Km , Vmax); PGs; cocoa pulp